Bioquímica sanguínea de três grupos : fisiculturistas usuários de esteróides anabólicos andrôgenicos, atletas praticantes de exercícios resistidos e sedentários - Maruyama, Marcos (2012)
Objective: Evaluate the effects of anabolic androgenic steroids (AAS) in blood biochemical markers. Subjects and Methods: We formed 03 groups with 08 volunteers in each: bodybuilders using AAS (A), athletes practicing resistance exercise (B) and sedentary (C). We analyzed hormones, enzymes, muscle, kidney and liver function, lipid profile and homocysteine. Results: In group A were increased growth hormone (GH) (p = 0.003), lactate dehydrogenase (LDH) (p = 0.002), creatine phosphokinase (CPK) (p = 0.003), urea (p = 0.006), creatinine (p = 0.003), aspartate aminotransferase (AST) (p = 0.007), alanine aminotransferase (ALT) (p = 0.009), low density lipoprotein-cholesterol (LDL-c) (p = 0.02) and reduced to sex hormone binding globulin (SHBG) (p = 0.0007), insulin (p = 0.03), high density lipoproteincholesterol (HDL-C) (p = 0.0004) and no change testosterone total and free, cortisol, leptin, total cholesterol, triacylglycerol (TAG), very low density lipoprotein-cholesterol, VLDL-C and homocysteine. Conclusion: The observed in this study suggests that AAS users are exposed to increased cardiovascular risk, kidney and liver.